Antibiotics-heavy metals combined pollution in agricultural soils: Sources, fate, risks, and countermeasures - Yuanxiang Shu; Donghao Li; Tong Xie; Ke Zhao; Lu Zhou; Fengxiang Li (Green Energy & Environment)
Agricultural soil is related to food security and human health, antibiotics and heavy metals (HMs), as two typical pollutants, possess a high coexistence rate in the environmental medium, which is extremely prone to inducing antibiotic-HMs combined pollution. Recently, frequent human activities have led to more prominent antibiotics-HMs combined contamination in agricultural soils, especially the production and spread of antibiotic resistance genes (ARGs), heavy metal resistance genes (MRGs), antibiotic resistant bacteria (ARB), and antibiotics-HMs complexes (AMCs), which seriously threaten soil ecology and human health. This review describes the main sources (Intrinsic and manmade sources), composite mechanisms (co-selective resistance, oxidative stress, and Joint toxicity mechanism), environmental fate and the potential risks (soil ecological and human health risks) of antibiotics and HMs in agricultural soils. Finally, the current effective source blocking, transmission control, and attenuation strategies are classified for discussion, such as the application of additives and barrier materials, as well as plant and animal remediation and bioremediation, etc., pointing out that future research should focus on the whole chain process of “source-process-terminal”, intending to provide a theoretical basis and decision-making reference for future research.